Portrait of Tuan Guru's Political Contest: An Analysis of Political Dynamics in Lombok, West Nusa Tenggara: Potret Kontestasi Politik Tuan Guru: Analisis terhadap Dinamika Politik di Lombok Nusa Tenggara Barat - M. Rusman Hadi; Sukron Azhari (Pesantren Reviews, 2023)
This article examines the portrait of the Tuan Guru's political contestation on the island of Lombok. In connection with the Tuan Guru's political contestation in Lombok, which was introduced by TGB, by giving a good impression to the community, it created great opportunities for all Tuan Gurus to participate in political contestations. This study uses a literature review by reviewing the literature, collecting data by searching for previous research, and looking at phenomena that occur in the field. And the theory used is the theory of moral leadership (moral leadership). The results of the research that Tuan Guru in Lombok has a great opportunity to participate in political contestation, by participating in this political contest, Tuan Guru is looking for supporters in very varied ways, such as in preaching, Tuan Guru goes to villages while continuing to apply da'wah. political ones. As well as Tuan Guru in seeking support or in dealing with political contestations, always provides an understanding to the community of the importance of choosing leaders by Islamic teachings. As a result, indirectly or unconsciously, the community was moved by the da'wah given by the teacher, in finding a religious leader, so that the congregation or the community agreed to win the guru in the political contestation in Lombok.